Traces of Buddhist architecture in Gupta and post-Gupta Bengal: evidence from inscriptions and literature - Reza, Mohammad Habib; Bandyopadhyay,Soumyen; Mowla, Azizul (© Mikes International, 2016)
This article was published in the Journal of Eurasian Studies [© 2015 Mikes International] and the definite version is available at : http://www.federatio.org/joes/EurasianStudies_0315.pdf The article website is at: http://www.federatio.org/joes.html